2011
DOI: 10.1016/j.virol.2011.02.019
|View full text |Cite
|
Sign up to set email alerts
|

A combination of polymorphic mutations in V3 loop of HIV-1 gp120 can confer noncompetitive resistance to maraviroc

Abstract: Maraviroc binds to the pocket of extracellular loops of the cell surface CCR5 and prevents R5 HIV-1 from using CCR5 as a coreceptor for entry into CD4-positive cells. To evaluate the contribution of the V3 loop structure in gp120 to maraviroc resistance, we isolated maraviroc-resistant variants from the V3 loop library virus (HIV-1(V3Lib)) containing a set of random combinations of 0-10 polymorphic mutations in vitro. HIV-1(V3Lib) at passage 17 could not be suppressed even at 10 μM (>1400-fold resistance), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…With other classes of antiretroviral drugs, there are hundreds of published reports on the in vitro selection of drug resistance by multiple research groups. However, in vitro patterns of resistance to CCR5 antagonists with overlapping CCR5 binding sites is limited to just seven published studies, yet each study describes a different mutational pathway to resistance (20,(23)(24)(25)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…With other classes of antiretroviral drugs, there are hundreds of published reports on the in vitro selection of drug resistance by multiple research groups. However, in vitro patterns of resistance to CCR5 antagonists with overlapping CCR5 binding sites is limited to just seven published studies, yet each study describes a different mutational pathway to resistance (20,(23)(24)(25)(35)(36)(37).…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that reverse mutations at positions 316 and 323 in the V3 loop of maraviroc-resistant HIV-1 variants to their original sequence restored wild-type susceptibility to maraviroc, while reversion of either mutation resulted in a partially sensitive virus with reduced maximal inhibition (Westby et al, 2007). In another recent study maraviroc-resistant variants were isolated from the V3 loop library virus (HIV-1(V3lib)) containing the T199K and T275M plus 5 mutations in the V3 loop, namely I304V; F312W; T314A; E317D; I318V (Yuan et al, 2011). Furthermore, the same study showed that the profile of HIV-1(JR-FL) pseudotype containing I304V/F312W/T314A/E317D/I318V ( Figure 7A) in the V3 loop alone revealed a typical non-competitive resistance to maraviroc (Yuan et al, 2011).…”
Section: Point Mutations Associated With Resistance To Attachment Inhmentioning
confidence: 99%
“…In another recent study maraviroc-resistant variants were isolated from the V3 loop library virus (HIV-1(V3lib)) containing the T199K and T275M plus 5 mutations in the V3 loop, namely I304V; F312W; T314A; E317D; I318V (Yuan et al, 2011). Furthermore, the same study showed that the profile of HIV-1(JR-FL) pseudotype containing I304V/F312W/T314A/E317D/I318V ( Figure 7A) in the V3 loop alone revealed a typical non-competitive resistance to maraviroc (Yuan et al, 2011). Generally, amino acids mutations in the V3 loop may include known polymorphism as well as novel substitutions, insertions, and deletions.…”
Section: Point Mutations Associated With Resistance To Attachment Inhmentioning
confidence: 99%
“…Although maraviroc (MVC), which is the first and currently only approved CCR5 antagonist for the treatment of CCR5-tropic (R5) HIV-1 infected patients, and another CCR5 inhibitor, vicriviroc (VCV), can efficiently suppress HIV-1 replication, drug-resistant variants can arise both in vitro and in vivo using drug-bound CCR5 for cellular entry (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The presence of MVC-resistant HIV-1 variants may be due to the outgrowth of pre-existing CXCR4-tropic (X4) HIV-1 viruses (19,20) or the selection of MVC-resistant R5 mutants (12,17).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of MVC-resistant HIV-1 variants may be due to the outgrowth of pre-existing CXCR4-tropic (X4) HIV-1 viruses (19,20) or the selection of MVC-resistant R5 mutants (12,17). MVCresistant mutations are commonly detected in the gp120 V3 loop and are strain-specific (3,12,16,21,22).…”
Section: Introductionmentioning
confidence: 99%